Applications of vision recognition and video intelligence - Mendoza, Jose (Henry Stewart Talks, 2026)
Retail, Product tagging, Security, Healthcare, Autonomous vehicles, Social media, Object tracking, Surveillance, AI, Facial recognition, Speech recognition